LB03.04: SPHYGMOMANOMETER CUFF CONSTRUCTION AND MATERIALS AFFECT TRANSMISSION OF PRESSURE FROM CUFF TO ARTERIAL WALL. FINITE ELEMENT ANALYSIS OF HUMAN PRESSURE MEASUREMENTS AND DICOM DATA. (June 2015) - Lewis, P.; Naqvi, S.; Mandal, P.; Potluri, P.
Abstract : Objective: Sphygmomanometer cuff pressure during deflation is assumed to equal systolic arterial pressure at the point of resumption of flow. Previous studies demonstrated that pressure decreases with increasing depth of soft tissues whilst visco-elastic characteristics of the arm tissue cause spatial and temporal variation in pressure magnitude. These generally used non-anatomical axisymmetrical arm simulations without incorporating arterial pressure variation. We used data from a volunteer's Magnetic Resonance (MR) arm scan and investigated the effect of variations in cuff materials and construction on the simulated transmission of pressure from under the cuff to the arterial wall under sinusoidal flow conditions. Design and method: Pressure was measured under 8 different cuffs using Oxford Pressure Monitor Sensors placed at 90 degrees around the mid upper arm of a healthy male. Each cuff was inflated 3 times to 155 mmHg and then deflated to zero with 90 seconds between inflations. Young's modulus, flexural rigidity and thickness of each cuff was measured. Using DICOM data from the MR scan of the arm, a 3D model was derived using ScanIP and imported into Abaqus for Finite Element Analysis (FEA). Published mechanical properties of arm tissues and geometric non-linearity were assumed. The measured sub-cuff pressures were applied to the simulated arm and pressure was calculated around the brachial arterial wall. which was loaded with a sinusoidal pressure of 125/85 mmHg. Results: FEA estimates of pressure around the brachial artery cuffs varied by up to 27 mmHg SBP and 17 mmHg DBP with different cuffs. Pressures within the cuffs varied up to 27 mmHg. Pressure transmission from the cuff to the arterial surface achieved a 95% transmission ratio with one rubber-bladdered cuff but varied between 76 and 88% for the others. Non-uniform pressure distribution around the arterial wall was strongly related to cuff fabric elastic modulus. Identical size cuffs with a separate rubber bladder produced peri-arterial pressure 14 mmHg higher than with a fabric bladder. Figure. No caption available. Conclusions: Wide variations of pressure within and under cuffs and at the artery wall interface, dependent on differing cuff materials and construction, may critically affect blood pressure measurement.